Mild synthesis of isoxazoline derivatives via an efficient [4 + 1] annulation reaction of transient nitrosoalkenes and sulfur ylides - Ting-Bi Hua (Nature Portfolio, 2021)
Abstract An efficient [4 + 1] annulation between α-bromooximes and sulfur ylides via in situ generation of nitrosoalkenes under mild basic reaction conditions has been developed, providing an expeditious and scalable approach to synthesize biologically interesting isoxazoline derivatives with good to excellent yields.